Guidelines for HPV-DNA Testing for Cervical Cancer Screening in Brazil - Zeferino,Luiz Carlos (2018)
Abstract Evidence-based clinical guidelines ensure best practice protocols are available in health care. There is a widespread use of human papillomavirus deoxyribonucleic acid (HPVDNA) tests in Brazil, regardless of the lack of official guidelines. On behalf of the Brazilian Association for the Lower Genital Tract Pathology and Colposcopy (ABPTGIC, in the Portuguese acronym), a team of reviewers searched for published evidence and developed a set of recommendations for the use of HPV-DNA tests in cervical cancer screening in Brazil. The product of this process was debated and consensus was sought by the participants. One concern of the authors was the inclusion of these tests in the assessment of women with cytologic atypia and women treated for cervical intraepithelial neoplasia (CIN). Testing for HPV is recommended in an organized screening scenario to identify women with precursor lesions or asymptomatic cervical cancer older than 30 years of age, and it can be performed every 5 years. It also has value after the cytology showing atypical squamous cells of undetermined significance (ASC-US) or low-grade squamous intraepithelial lesions (LSILs) as a triage test for colposcopy, in the investigation of other cytological alterations when no abnormal findings are observed at colposcopy, seeking to exclude disease, or, further, after treatment of high-grade cervical intraepithelial neoplasia, to rule out residual disease.